Model Pembelajaran Discovery Learning untuk Meningkatkan Motivasi Belajar Peserta Didik - Fitra Andayani Bahir; Inanna Inanna; Muhammad Hasan; Thamrin Tahir; Rahmatullah Rahmatullah (Indonesian Journal of Social and Educational Studies, 2020)
Implementation of Discovery Learning Model to Increase Student Motivation Based on Constructivism Class X IIS SMA Negeri 1 Campalagian Polewali Mandarn Regency. This study aims to increase motivation towards teaching and learning activities of educators and students as well as knowing the response of students to the Constructivism-based Discovery Learning Model in Economy Class X IIS SMA Negeri 1 Campalagian, Polman Regency. This type of research is a classroom action research. The subject of this research is Class X IIS 5 SMA Negeri 1 Campalagian, totaling 30 students. Data collection techniques using observations and interviews and questionnaires. Observation is used to determine the motivation for the activities of educators and students in learning activities, and interviews are conducted to determine the teacher's response to efforts to increase learning activities, a set of questionnaires are used to determine the response of students to the learning model implemented. The indicators of the success of the action are marked by a minimum of 75% of the total number of students in the good and very good categories (≥76% of the activities observed). The results of this study indicate that the implementation of the Constructivism-Based Discovery Learning Model can increase motivation towards the activities of educators and students. The activities of educators in the first cycle were 71.88% in the sufficient category, while the activities of students in the first cycle were 76.78% in the good category. The activities of educators and students have increased in cycle II during the learning process, educators become 85.93% in the very good category and students are in the 85.71% category of Good. The response of students to the constructivism-based Discovery learning model can be seen in the indicators that have been made, the percentage of values obtained is 84.82% in the good category.